Preparation and microcontact printing of platinum and palladium thin films - Wisser, Florian M.; Schumm, Benjamin; Meier, Andreas; Engel, Tom; Grothe, Julia; Kickelbick, Guido; Kaskel, Stefan (Journal of Materials Chemistry C, 2013)
Thin palladium and platinum films were prepared using a polymeric precursor method. For the first time, down to 30 nm thick films were achieved by this method. A precursor solution consisting of ethylene glycol, citric acid, a metal salt and the corresponding acid was deposited by spin coating onto various substrates. The thermal decomposition behavior of these precursors was characterized by thermal analysis methods. Dried and calcined films were characterized by XRD, UV-Vis and IR spectroscopy as well as resistance measurements to get more information about the film formation. The specific resistance of the phase pure platinum films was as low as 1.1 × 10 -7 Ω m and that of the palladium films was as low as 6.0 × 10-7 Ω m. In addition, a platinum precursor was used for microcontact printing. Regular line patterns with widths between 800 nm and 15 μm were achieved, as could be shown by AFM and SEM. © The Royal Society of Chemistry 2013.
CRIS-Team Scopus Importer:2023-03-20